Alcohol and age. (5th January 2018) - Crome, Ilana B; Crome, Peter
Abstract: Alcohol consumption constitutes a substantial burden of disease. Older people are being admitted to hospital for alcohol problems in increasing numbers. A recent systematic review reports cautious supportive evidence for primary prevention interventions in reducing excessive alcohol consumption in older drinkers, but does not focus on treatment of dependent drinkers. The evidence base for treatment interventions for dependent drinkers is comparatively limited, but it is growing. In addition to brief interventions, specialist outpatient treatment and inpatient treatment have been evaluated. The responses of older people to treatment are promising: they want to abstain, they have the capacity to change, they respond well to brief advice and motivational enhancement therapy, they achieve improvements at least as comparable to younger counterparts—and sometimes better—and they do have the prospect of long-term recovery. There is a need to develop services tailored to the needs of older substance misusers. Education of the workforce, including medical students and other health care professionals, is the key. Collaboration and coordination of services, training, research and policy are essential. There are very few designated services for older substance misusers in the UK and only 7% of older people who need treatment for alcohol problems access them. There is a massive gap in the whole gamut of research from basic to clinical research in this vulnerable patient population: this has to be developed if management is to be effective and up to date.